Azadirachta indica treatment on the congenital malformations of fetuses from rats - Dallaqua, Bruna [UNESP]; Saito, Felipe Hiroshi [UNESP]; Rodrigues, Tiago; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina [UNESP] (Elsevier B.V., 2013)
Ethnopharmacological relevance: Azadirachta indica A. Juss, popularly known as neem, presents medicinal and insecticide properties. However, the repercussions of the neem maternal treatment on fetal development should be investigated. Thus, the aim of this study was to evaluated the effects of Azadirachta indica (neem) on the frequency of congenital malformations in fetuses from rats.Materials and methods: Pregnant rats were randomly distributed into three experimental groups: NT=non-treated; TOil=treated with neem seed oil (1.2 mL/day); TAP=treated with active principle of Azadirachta indica (azadirachtin-1.0 mg/mL/day). The neem oil (1.2 mL/day) or azadirachtin (1.0 mg/mL/day) treatments were orally administered throughout pregnancy. Blood samples were collected on days 0, 7, 14 and 20 of pregnancy Oral glucose test tolerance (OGTT) was performed at day 17 of pregnancy for estimation of total area under the curve (AUC). At term, the fetuses were collected and external and internal (visceral and skeletal) malformations were analyzed.Results: The data showed that the dams treated with neem seed oil and Azadirachtin had no significant change in glucose levels and AUC. It was also verified that neem oil treatment contributed to increase the frequency of malformation/variation, in particular the visceral in their fetuses, while neither significant result was observed in TAP group.Conclusion: In conclusion, neem seed oil treatment administered during pregnancy caused abnormalities in rat fetuses, showing teratogenic effect but the Azadirachtin (active principle) presented no impairment in the fetuses. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Azadirachta indica; Neem; Pregnancy; Rat; Anomaly